Application of Multimedia Tools in Student Achievement - Khadka, Suresh Kumar; Bhandari, Reg Bahadur (ILAM इलम, 2024)
Information and communication technologies (ICT) have been a way of life. ICT can be used in various aspects and areas. We have been using ICT in agriculture, business, education, health, finance, banking, etc. Across the past thirty years, ICT has fundamentally changed the practices and procedures of nearly all forms of enterprise within business and governance. The study aimed to measure the effect of using multimedia tools in the "Statistics and Computer Application" curriculum on the students’ academic achievement. The researcher has implemented quantitative research methodology and the experimental method (true experimental design) as research design tools. To carry out the study, the study area was the secondary school of Salyan, pursuing ISc. Ag., and the sample size was 80 students majoring in statistics and computer applications. The analysis and interpretation of the data above yield the result that the development of science education has been rather slow. There is a significant difference between the results of the control group (taught using traditional teaching methods) and the experimental group (taught using ICT multimedia techniques), i.e., the experimental group has better quality in statistics and computer application than the control group. So, if we can implement ICT multimedia techniques in teaching learning activities, it should be provided with adequate instructional materials and initiatives involving them in teaching learning, decision-making processes, training, workshops, and implementing 21st-century-based learning. Several factors, like student behaviour, ICT environment at school, digital illiteracy of parents, digital awareness, home environment, computer lab, projector, email internet facilities, teacher education, and teacher training, have affected student achievement in learning in higher secondary schools. From the analysis of the study, it has been concluded that student achievement was better in the experimental group than in the control group.